Diffusion of an innovation: growth in video capsule endoscopy in the U.S. Medicare population from 2003 to 2019 - Andrew J. Read; Michael D. Rice; Jason R. Baker; Akbar K. Waljee; Sameer D. Saini (BMC, 2022)
Abstract Background Video capsule endoscopy (VCE), approved by the U.S. Food and Drug Administration (FDA) in 2001, represented a disruptive technology that transformed evaluation of the small intestine. Adoption of this technology over time and current use within the U.S. clinical population has not been well described. Methods To assess the growth of capsule endoscopy within the U.S. Medicare provider population (absolute growth and on a population-adjusted basis), characterize the providers performing VCE, and describe potential regional differences in use. Medicare summary data from 2003 to 2019 were used to retrospectively analyze capsule endoscopy use in a multiple cross-sectional design. In addition, detailed provider summary files were used from 2012 to 2018 to characterize provider demographics. Results VCE use grew rapidly from 2003 to 2008 followed by a plateau from 2008 to 2019. There was significant variation in use of VCE between states, with up to 10-fold variation between states (14.6 to 156.1 per 100,000 enrollees in 2018). During this time, the adjusted VCE use on a population-adjusted basis declined, reflecting saturation of growth. Conclusions Growth of VCE use over time follows an S-shaped diffusion of innovation curve demonstrating a successful diffusion of innovation within gastroenterology. The lack of additional growth since 2008 suggests that current levels of use are well matched to overall population need within the constraints of reimbursement. Future studies should examine whether this lack of growth has implications for access and healthcare inequities.